Pelatihan Manajemen Stres untuk Mengatasi Work Family Conflict pada Guru - Theodora Takalapeta; Juliana M. Y. Benu (Journal of Health and Behavioral Science, 2019)
Women with professions as a teacher and married have many roles, both in the family and in the work environment. The many roles that are carried out often lead to work-family conflict. A work-family Conflict is a form of conflict between roles where the pressure of roles in work and roles in the family are conflicting in several ways. The conflict that is experienced is not resolved and will cause work stress and affect the balance of work and family. Therefore, stress management training is given three (3) aspects, they are knowledge, skills, and attitude to 12 participants. The results are, all participants experienced increased knowledge about stress management. In addition, all participants were also able to apply emotional coping stress and problem solving coping when faced with stressors.